Use of acoustic myography to evaluate forelimb muscle function in retriever dogs carrying different mouth weights - Weber, Melissa A.; Manfredi, Jane M.; Tomlinson, Julia E. (Frontiers in Veterinary Science, 2022)
Objectives To evaluate the effect of mouth weight on gait and relative function of forelimb muscles in retriever hunting dogs as a possible explanation for biceps tendinopathy. Methods Ten sound retriever dogs underwent acoustic myography, measuring efficiency (E-score), spatial summation (S-score), and temporal summation (T-score) during walk and trot on a pressure-sensitive walkway while carrying a 0 lb (0 kg), 1 lb (0.45 kg), and 3.2 lb (1.45 kg) mouth weight. Gait data included total pressure index (TPI), step length, and stance time. Statistics included a mixed effects model significant at p < 0.05. Results Forelimb TPI increased with increasing weight. There was no significant change in individual muscle parameters in response to weight. Significance was found in between-muscle comparisons. For walk, T-score was significantly lower in triceps vs. brachiocephalicus with 1 lb, not with 3.2 lb., S-score was significantly lower in the biceps at 0, 1 lb, and triceps at 0 lb. when compared to brachiocephalicus, E-score was significantly lower in deltoideus vs. brachiocephalicus at trot with l and 3.2 lb. There was an overall significant effect of muscle on T-score at trot, but no individual muscle comparison was significant. Conclusion Forelimb load increases with mouth weight. Deltoideus had a longer contraction time in response to increasing weight at trot when compared to brachiocephalicus. The biceps muscle did not show increased work in response to increasing weight. Clinical relevance The underlying etiology of biceps tendinopathies in retriever dogs remains uncertain but is not due to increasing weight.